Vascular Changes in Bleomycin-Induced Scleroderma - Yamamoto, Toshiyuki (Hindawi Publishing Corporation, 2011)
Systemic sclerosis (SSc) is characterized by vascular injury, immunological abnormalities, and fibrosis of the skin as well as various internal organs. Vascular impairment is the early manifestation and plays a fundamental role in the pathogenesis of SSc. Recent studies suggest that complex interactions among the endothelial cells, pericytes, smooth muscle cells, and fibroblasts are involved in the systemic vasculopathy in SSc, and histological feature of proliferation of vascular wall is seen in the lesional scleroderma skin at the late stage of disease. One of the most representative mouse models for scleroderma is the bleomycin-induced scleroderma; however, aspects of vascular alteration have not been described in detail so far. A number of studies have shown that bleomycin stimulates endothelial cells and fibroblasts to induce proinflammatory and fibrogenic cytokines, apoptosis, reactive oxygen species, and so on. This paper makes a focus on the vascular involvement in the bleomycin-induced murine scleroderma.